An Uncommon Carboxyl‐Decorated Metal–Organic Framework with Selective Gas Adsorption and Catalytic Conversion of CO2. Issue 4 (13th December 2017) - Li, Yong‐Zhi; Wang, Hai‐Hua; Yang, Hong‐Yun; Hou, Lei; Wang, Yao‐Yu; Zhu, Zhonghua
Abstract: A new three‐dimensional (3D) framework, [Ni(btzip)(H2 btzip)]⋅ 2 DMF⋅ 2 H2 O (1 ) (H2 btzip=4, 6‐bis(triazol‐1‐yl)isophthalic acid) as an acidic heterogeneous catalyst was constructed by the reaction of nickel wire and a triazolyl‐carboxyl linker. Framework1 possesses intersected 2D channels decorated by free COOH groups and uncoordinated triazolyl N atoms, leading to not only high CO2 and C2 H6 adsorption capacity but also significant selective capture for CO2 and C2 H6 over CH4 and CO in 273–333 K. Moreover, 1 reveals chemical stability toward water. Grand Canonical Monte Carlo simulations confirmed the multiple CO2 ‐ and C2 H6 ‐philic sites. As a result of the presence of accessible Brønsted acidic COOH groups in the channels, the activated framework demonstrates highly efficient catalytic activity in the cycloaddition reaction of CO2 with propylene oxide/4‐chloromethyl‐1, 3‐dioxolan‐2‐one/3‐butoxy‐1, 2‐epoxypropane into cyclic carbonates. Abstract : Through employing a triazolyl‐carboxyl linker, a stable porous Ni metal–organic framework (MOF) was constructed, which contains free carboxyl groups in channels and reveals not only high CO2 and C2 H6 loadings but also significant selective capture for CO2 and C2 H6 over CH4 and CO, as well as highly efficient catalytic activity in the cycloaddition reaction of CO2 with epoxides. The multi‐point framework–CO2 /C2 H6 interactions were confirmed by Grand Canonical Monte Carlo simulations (see scheme).